A PIK3R2 Mutation in Familial Temporal Lobe Epilepsy as a Possible Pathogenic Variant - Wang, Yishu; Peng, Jing; Bai, Shuwei; Yu, Haojun; He, Hong; Fan, Chunxiang; Hao, Yong; Guan, Yangtai (Frontiers in Genetics, 2021)
Temporal lobe epilepsy (TLE), the most common form of medically refractory focal epilepsy in adults, often requires surgery to alleviate seizures. By using next-generation sequencing, we identified a PIK3R2 mutation (NM_005027.4: c.265C>T; NP_005018.2: p.Arg89Cys) in a family with mesial temporal lobe epilepsy. PIK3R2 encodes p85β, the regulatory subunit of Class IA PI3K and the mutation we identified in PIK3R2 seems to function unexpectedly as a possible pathogenic variant. The mutation is predicted to be potentially pathogenic by multiple bioinformatics tools. Through a functional assay, we verified that the mutation enhances the function of PI3K in induced pluripotent stem cells (iPSCs) derived from peripheral blood mononuclear cells (PBMCs) of the proband. Finally, pathological testing of the resected temporal lobe cortex showed that the expression of PIK3R2 was significantly higher in patients with refractory temporal lobe epilepsy than in those of non-epileptic diseases as a control group. It can be inferred that PIK3R2 might play an important role in the development of TLE.